Mewcifer
  • Mewcifer
I need help please An equation is shown below: 8(2x – 14) + 13 = 4x – 27 Part A: Write the steps you will use to solve the equation, and explain each step. (6 points) Part B: What value of x makes the equation true? (4 points)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
http://www.geteasysolution.com/ Easy way to find your answer and it shows work! :D
anonymous
  • anonymous
It's basically a calculator. :>
Mewcifer
  • Mewcifer
Thanks so much, do you think you can help me with another one? @StudyBuggTori

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Shoot! :> I'll try my best.
Mewcifer
  • Mewcifer
An equation is shown below: 8x + 2(x – 7) = 7x + 3x – 14 Part A: Solve the equation and write the number of solutions. Show all the steps. (6 points) Part B: Name one property you used to solve this equation. (4 points)
Mewcifer
  • Mewcifer
@StudyBuggTori
anonymous
  • anonymous
You could use the same website for that one too. I know what I'm saying isn't much help but all your answers are there if you plug it in.
Mewcifer
  • Mewcifer
It's not working
anonymous
  • anonymous
Simplifying 8x + 2(x + -7) = 7x + 3 + -14 Reorder the terms: 8x + 2(-7 + x) = 7x + 3 + -14 8x + (-7 * 2 + x * 2) = 7x + 3 + -14 8x + (-14 + 2x) = 7x + 3 + -14 Reorder the terms: -14 + 8x + 2x = 7x + 3 + -14 Combine like terms: 8x + 2x = 10x -14 + 10x = 7x + 3 + -14 Reorder the terms: -14 + 10x = 3 + -14 + 7x Combine like terms: 3 + -14 = -11 -14 + 10x = -11 + 7x Solving -14 + 10x = -11 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -14 + 10x + -7x = -11 + 7x + -7x Combine like terms: 10x + -7x = 3x -14 + 3x = -11 + 7x + -7x Combine like terms: 7x + -7x = 0 -14 + 3x = -11 + 0 -14 + 3x = -11 Add '14' to each side of the equation. -14 + 14 + 3x = -11 + 14 Combine like terms: -14 + 14 = 0 0 + 3x = -11 + 14 3x = -11 + 14 Combine like terms: -11 + 14 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
anonymous
  • anonymous
There you go. and here is the link for the first question. http://www.geteasysolution.com/8(2x-14)+13=4x-27

Looking for something else?

Not the answer you are looking for? Search for more explanations.